2014
DOI: 10.1117/1.jbo.19.11.116005
|View full text |Cite
|
Sign up to set email alerts
|

Low coherence interferometry approach for aiding fine needle aspiration biopsies

Abstract: Abstract. We present portable preclinical low-coherence interference (LCI) instrumentation for aiding fine needle aspiration biopsies featuring the second-generation LCI-based biopsy probe and an improved scoring algorithm for tissue differentiation. Our instrument and algorithm were tested on 38 mice with cultured tumor mass and we show the specificity, sensitivity, and positive predictive value of tumor detection of over 0.89, 0.88, and 0.96, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…There is also the potential to incorporate a forward-facing OCT probe within the biopsy needle to reduce risk during needle insertion. These designs have already been demonstrated for non-neurosurgical applications ( 44 ), and our team has demonstrated a forward-facing optical design similar to that used in this current paper ( 60 ). We note that the diameter of the distal focusing optics of the probe is only 250 μm, and the body of the probe is 900 μm in diameter due to a protective Hytrel jacket around the fiber.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…There is also the potential to incorporate a forward-facing OCT probe within the biopsy needle to reduce risk during needle insertion. These designs have already been demonstrated for non-neurosurgical applications ( 44 ), and our team has demonstrated a forward-facing optical design similar to that used in this current paper ( 60 ). We note that the diameter of the distal focusing optics of the probe is only 250 μm, and the body of the probe is 900 μm in diameter due to a protective Hytrel jacket around the fiber.…”
Section: Discussionmentioning
confidence: 84%
“…This has necessitated the development of miniaturized fiber-optic probes, which may be incorporated into the hypodermic needle to provide guidance near the distal tip of the needle as it is inserted at depth (41). Previous studies have demonstrated the use of these imaging needles in a range of tissues, including breast (42)(43)(44), lung (45,46), and brain (47,48). While the design of these probes is well established, their use in human studies is very limited, with most work restricted to animal or ex vivo human tissue, and no previous studies have demonstrated their use for in vivo human brain.…”
Section: Introductionmentioning
confidence: 99%
“…Another major advantage of OCT is that the technology evolved to a needle‐based platform, enabling microscopic resolution 3D optical biopsies of tissue. These ultra‐thin high resolution needle‐based imaging platforms have already proven their efficacy in the lymph nodes , lung , breast and skeletal muscle . It is expected that in the future, technology will become faster, and resolutions will become higher (to the micrometer level), resulting in even higher diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Such technologies include Raman spectroscopy, dynamic light scattering, optical coherence tomography (OCT), etc. [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Among them, OCT has shown significant promise due to its ability to assess true tissue morphology within relatively large volumes of tissue, such as the size of the biopsy cores, at a higher speed than of the other modalities.…”
Section: Introductionmentioning
confidence: 99%